Comparison of oxygen supplementation by nasal cannula with suction versus air insufflation without suction under drapes during monitored anesthesia care in adult cataract surgery-A randomized non-inferiority trial - Subramaniam Shanmugam Arivazhakan; Hemavathi Balachander; Sakthirajan Panneerselvam; Kirthiha Govindaraj; Priya Rudingwa (Saudi Journal of Anaesthesia)
Background: Patients with multiple co-morbidities undergoing cataract surgery are at risk of hypoxia and hypercarbia secondary to the rebreathing of the accumulated carbon dioxide under the surgical drapes. They are also at risk of fire accidents due to the hyperoxic condition secondary to oxygen supplementation. Objectives: The main aim of the study was to determine the lowest level of hemoglobin oxygen saturation while providing medical air in comparison with oxygen. Our hypothesis is that providing medical air will be non-inferior to oxygen administration in preventing hypoxia and rebreathing in these patients. Methods: This randomized non-inferiority trial was conducted in a single center Tertiary care hospital, over a study period of March 2020 to February 2021. Fifty-six adult patients with equal gender distribution undergoing cataract surgery with multiple comorbid conditions without sedative premedications were included in the study and randomized into either Group “O” (n = 28) who received oxygen @ 4 l min-1 through a nasal cannula with suction, and Group “A” (n = 28) who received medical air @10 l min-1 through the circle breathing system under the drapes. The main outcome measured was the lowest hemoglobin oxygen saturation (SPO2), the highest end-tidal carbon dioxide (hETCO2), and the highest fraction of inspired carbon dioxide levels (hFiCO2). Results: The lowest mean SPO2 measured was found to be similar between Group O and Group A with 98.8 ± 0.7 and 98.4 ± 0.9 (P = 0.081), respectively. The highest mean ETCO2 and mean FiCO2 values were also comparable between the Group O versus Group A with 32.8 ± 2.1 versus 33.3 ± 2.2 (P = 0.464), and 4.5 ± 1.4 versus 4.8 ± 1.8 (P = 0.464) respectively. Conclusion: We conclude that the supplementation of compressed medical air under surgical drapes is non-inferior to nasal oxygen supplementation under regional anesthesia without causing hypoxia and hypercarbia by conserving valuable hospital resources.